Impact of Medicaid Policy for Non-Dentist Providers on the Oral Health of Publicly Insured Children - Kranz, Ashley M (Matern Child Health J, 2019)
OBJECTIVE: Fluoride varnish (FV) applications among non-dentist primary care providers has increased due to state Medicaid policies. In this study we examine the impact of FV policies on the oral health of publicly insured children aged 2 to 6 years old. METHODS: Using three waves of the National Survey of Children’s Health (2003, 2007, 2011/12), we used a logistic regression model with state and year fixed effects, adjusting for relevant child characteristics, to examine the association between years since a state implemented a FV policy and the odds of a publicly insured child having very good or excellent teeth. We compared children with public insurance in states with FV policies to children with public insurance in states without FV policies, controlling for the same difference among children with private insurance who were unlikely to be affected by Medicaid FV policies. RESULTS: Among 68,890 children aged 2–6 years, 38% had public insurance. Compared to privately insured children, publicly insured children had significantly lower odds of having very good or excellent teeth (odds ratio (OR)=0.70, 95% CI=0.62–0.81). Publicly insured children in states with FV policies implemented for four or more years had significantly greater odds of having very good or excellent teeth (OR=1.28, 95% CI=1.03–1.60) compared to publicly insured children in states without FV policies. CONCLUSIONS FOR PRACTICE: State policies supporting non-dental primary care providers application of FV were associated with improvements in oral health for young children with public insurance.